Effects of varying fiber length towards packet delay in Passive Optical Network - Radzi N.A.M.; Ridwan M.A.; Abdullah F.; Din N.M.; Al-Mansoori M.H.; Abidin H.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electronic equipment; Fibers; Oscillators (electronic); Packet networks; Passive networks; Radio communication; Software radio; Testbeds; Cost saving; Fiber length; National Instruments; Nonlinear effect; Packet delay; Peripheral interface controllers; Real estate; Passive optical networks